2023
DOI: 10.1111/os.13657
|View full text |Cite
|
Sign up to set email alerts
|

Acceptable Fusion Rate of Single‐Level OLIF Using Pure Allograft Combined with Posterior Instrumentation through the Wiltse Approach: A 2‐Year Follow‐Up Study

Abstract: Objective Autogenic bone grafts have shown successful fusion rates in the treatment of degenerative lumbar disorders, but taking too many autogenic bones may result in donor site ischemia or infection. This study aimed to evaluate the outcomes of single‐level oblique lumbar interbody fusion (OLIF) using pure allograft combined with posterior pedicle screw instrumentation through the Wiltse approach. Methods A retrospective case analysis was performed on a series of consecutive patients who received a single‐le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The concept of fusion rate after lumbar interbody fusion is subject to interpretation in various studies; different studies have used nonidentical and heterogeneous criteria to assess bone fusion [ 11 , 16 , 21 , 26 - 28 ]. Many studies regarded patients without clear pseudoarthrosis as having successful fusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The concept of fusion rate after lumbar interbody fusion is subject to interpretation in various studies; different studies have used nonidentical and heterogeneous criteria to assess bone fusion [ 11 , 16 , 21 , 26 - 28 ]. Many studies regarded patients without clear pseudoarthrosis as having successful fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Autografts remain the gold standard material, displaying successful fusion rates in the treatment of degenerative lumbar disorders. However, procuring too many autogenic bone grafts may result in donor site morbidities, especially resulting in pain or infection [ 5 , 15 , 16 ]. The use of other alternative osteobiologics in spine surgery is believed to improve pain, fusion rates, and clinical outcomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have indicated a fusion rate of 84% or higher with OLIF surgery. [39]. The most frequent complications after OLIF surgery were endplate fracture/collapse (18.7%), transient lumbar muscle weakness and thigh numbness (13.5%), segmental artery injury (2.6%), surgical site infection (1.9%), and the need for reoperation (1.9%).…”
Section: Oblique Lif (Olif)mentioning
confidence: 99%